New Therapies for Sepsis - Cunnington, Aubrey; Nadel, Simon (Current Topics in Medicinal Chemistry, 2008)
Sepsis is a common clinical problem that is responsible for an increasing number of deaths. Many new therapies for severe sepsis have been developed but few have shown benefit in rigorous clinical trials. To date the most successful therapies are relatively simple clinical interventions: appropriate broad spectrum antibiotics; early goal directed therapies to restore tissue oxygen delivery; physiological dose hydrocortisone in patients with relative adrenal insufficiency; intensive insulin therapy to maintain normoglycemia; and lung-protective ventilation strategies. The only adjunctive therapy supported by strong evidence of benefit is Activated Protein C. Experimental therapies are being developed with improved in vitro and animal models and better understanding of the pathophysiology of sepsis in humans. Neutralization of the triggers of inflammation, such as endotoxin, and inhibition of the signal transduction mechanisms are promising new strategies. Statins may be beneficial in prevention of sepsis and as adjunctive treatments. Reconstitution of the immune response with interferon-gamma or granulocyte-macrophage colony stimulating factor may reverse immunoparesis in severe sepsis. Many other molecular targets have been identified for possible therapeutic intervention, but there are still fundamental difficulties to be overcome in demonstrating efficacy in clinical trials.